Effects of process parameters on the evaporative pattern casting of scrap aluminum–RHA composites - Rudi Siswanto; Abdul Ghofur; Rachmat Subagyo; Mastiadi Tamjidillah; Mahmud Mahmud; Ma’ruf Ma’ruf; Adi Nordiman (Teknomekanik, 2026)
This study investigates the fabrication and characterization of aluminium matrix composites reinforced with rice husk ash (RHA), using scrap aluminium as the base material and evaporative pattern casting as the manufacturing method. The work evaluates the effects of three key independent variables: pouring temperature, aluminium (Al)-RHA composition ratios, and styrofoam pattern thickness on the resulting composite properties. The dependent variables examined include surface roughness, Brinell hardness, and dimensional shrinkage-expansion. Experimental results show that increasing the pouring temperature and adjusting the composition ratio significantly influence the mechanical and physical properties of the composites. The highest hardness (45.6 HB) and fluidity (252.65 mm) were achieved at a 60:40 composition ratio and a pouring temperature of 750 °C, albeit at the cost of increased porosity. Additionally, the styrofoam pattern thickness was found to affect the dimensional stability and surface roughness of the composites, with thicker patterns resulting in higher surface roughness. This study highlights the potential of utilizing rice husk ash as a reinforcing material in aluminium matrix composites, offering a sustainable approach to improving material properties. The findings suggest that an optimal balance of composition ratio, pouring temperature, and pattern thickness is crucial to achieving desirable mechanical and physical characteristics, with implications for advanced manufacturing processes in the materials industry.